2010
DOI: 10.1242/dev.047654
|View full text |Cite
|
Sign up to set email alerts
|

TheC. eleganshomolog of nucleoporin Nup98 is required for the integrity and function of germline P granules

Abstract: All transgenes were driven by the pie-1 promoter (maternal expression), unless otherwise indicated, and were constructed by Gateway cloning (Invitrogen) (Landy, 1989). Coding sequences and predicted 3ЈUTRs were amplified from N2 genomic DNA (npp-7, npp-9, npp-10). Gene structure of npp-10 was analyzed by cDNA sequencing [ends of cDNAs were verified by 5Ј RACE with SL1 primer, and 3Ј RACE with oligo(dT) primer], and the corrected mRNA sequence, including four additional 5Ј exons, was submitted to GenBank (acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 49 publications
(61 reference statements)
0
59
0
Order By: Relevance
“…Ultrastructural analysis of P granules in germ cells of adult hermaphrodite gonads has shown that P granules are tightly associated with nuclear pores on the nuclear envelope (Pitt et al, 2000). In addition, a nuclear pore component, Nup98, has been shown to be essential for the perinuclear association of PGL-1 (Voronina and Seydoux, 2010). Furthermore, FG repeats, a hallmark of many nuclear pore proteins, have been found in another family of P-granule proteins comprising GLH-1, -2 and -4 (Kuznicki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural analysis of P granules in germ cells of adult hermaphrodite gonads has shown that P granules are tightly associated with nuclear pores on the nuclear envelope (Pitt et al, 2000). In addition, a nuclear pore component, Nup98, has been shown to be essential for the perinuclear association of PGL-1 (Voronina and Seydoux, 2010). Furthermore, FG repeats, a hallmark of many nuclear pore proteins, have been found in another family of P-granule proteins comprising GLH-1, -2 and -4 (Kuznicki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…OCF3: unc-119(ed3); jjIs1092[pNUT1:npp-1::gfp + unc-119(+)]; ltIs37 [pAA64: pie-1p::mCHERRY::his-58 + unc-119 (+)] (Golden et al, 2009) ; OCF17: unc-119(ed3); ocfIs3[pie-1 prom::GFP::npp-5::pie-1 3′UTR +unc119 (+)]; JH2184: unc-119(ed3); axIs1595 [pie-1 prom::GFP:npp-9::npp-9 3′UTR] (Voronina and Seydoux, 2010); AZ212: unc-119(ed3); [pie-1 prom::GFP::hisH2B::pie-1 3′UTR +unc119 (+)]; OCF22: unc-119(ed3); ocfIs5[pie-1 prom::mCherry::npp-1::pie-1 3′UTR +unc119 (+)]; OCF15: unc-119(ed3); ocfIs2[pie-1 prom::mCherry::sp12::pie-1 3′UTR +unc119 (+)]; OCF25(expressing mCherry::NPP-1,GFP::NPP-5): generated by crossing OCF22 with OCF17; OCF26(expressing mCherry::NPP-1,YFP::LMN-1): generated by crossing OCF4 (Golden et al, 2009) with OCF22 and backcrossing with N2; OCF28(expressing mCherry::NPP-1,GFP::TBA-2): generated by crossing OCF22 with OD57: unc-119(ed3); ltIs37 [pAA64: pie-1p::mCHERRY::his-58 + unc-119 (+)]; ltIs25 [pAZ132; pie-1p::GFP::tba-2 + unc-119 (+)] (McNally et al, 2006); OCF16(expressing GFP::NPP-1, mCherry::SP12): generated by crossing OCF15 with LW1094: unc-119(ed3); jjIs1094[pNUT1:npp-1::gfp + unc-119(+)]; MSN146(expressing CR::SP12, GFP::TBA-2): unc-119(ed3) III; ltIs76 [pAA178: pie-1p::mCHERRY::sp12 + unc-119 (+)]; ltIs25 [pAZ132; pie-1p::GFP::tba-2 + unc-119 (+)]. The nucleoporin-GFP and mCherry fusion proteins used in this study were not tested for rescuing the functionality of mutant alleles and therefore it is not known whether they are functional.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular interactions that lead to the liquid-like behavior of P-granules was addressed by two recent studies that explored the molecular requirements for the formation of P-granules (Updike et al , 2011; Updike and Strome, 2009; Voronina and Seydoux, 2010). Both studies made the important observation that several proteins present in P-granules (the Vasa related proteins GHL-1, GHL-2 and GLH-3) contain repeats of the amino acids phenylalanine and glycine, and these were required in GLH-1 for granule formation (Updike et al, 2011).…”
Section: Formation and Structure Of Rna Granulesmentioning
confidence: 99%
“…Consistent with a link between the nuclear pore and P-granules, P-granules exhibited a size exclusion of fluorescent dextrans, similar to the nuclear pore (Updike et al, 2011). In addition, RNAi against a subset of nuclear pore proteins disrupted P-granule formation (Voronina and Seydoux, 2010). Furthermore, GFP-fusions of several nuclear pore proteins colocalized with P-granules, and mutation of the C. elegans Nup98 homolog disrupted P-granule formation.…”
Section: Formation and Structure Of Rna Granulesmentioning
confidence: 99%
See 1 more Smart Citation